Comprehensive analysis of gut microbiota and fecal metabolites in patients with autism spectrum disorder - Ruijuan Zheng; Silu Huang; Pengya Feng; Simeng Liu; Miaomiao Jiang; Huijuan Li; Pengyuan Zheng; Pengyuan Zheng; Yang Mi; Yang Mi; Enyao Li (Frontiers in Microbiology)
IntroductionAutism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by deficits in social communication and the presence of restricted, repetitive behaviors or interests. Studies have revealed that gut microbiota and their metabolism play important roles in ASD, and become the underlying mechanisms of ASD.MethodsIn this study, we performed long-read 16S rRNA sequencing and untargeted metabolomics to comprehensively characterize the profiles of gut microbiota and fecal metabolites in 34 ASD patients and 18 healthy controls. The associations between gut microbiota, fecal metabolites and clinical symptoms were analyzed to screen related biomarkers for ASD.ResultsThe results showed the similarity of the overall microbial richness and diversity between ASD patients and controls, however, some specific bacterial taxa exhibited significant differences, including Klebsiella and Escherichia-Shigella at genera level, and Clostridium-sporogenes, Escherichia-coli-O157H7 and Bacteroides-ovatus at species level. The fecal metabolomics validated that a lot of metabolites had significantly differential levels, including a series of organic acids, amino acids and dopamine.DiscussionThe associations of gut microbiota and fecal metabolites might shed new light on the pathogenesis of ASD and help us to understand the importance of gut microbiota as potential biomarkers and therapeutic targets in the development of ASD.